2011
DOI: 10.1177/1350650111405115
|View full text |Cite
|
Sign up to set email alerts
|

The influence of base oil polarity and slide–roll ratio on additive-derived reaction layer formation

Abstract: Functional additives, particularly extreme-pressure and antiwear additives, in formulated oil will compete to adsorb and form a protective layer in tribological contacts. The thickness of the layer is determined by the equilibrium between the formation and removal processes. In this article, the interactions between additives and base oil molecules and operating conditions influence friction and wear are studied. One polar (ester oil) and one non-polar (poly-a-olefin) commercial base oil blended with zinc dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 40 publications
(51 reference statements)
3
33
0
Order By: Relevance
“…They also showed that the growth rate is governed by the shear stress, rather than the normal stress. This fact is confirmed by experiments showing that tribo-films do not grow in pure rolling contacts, not even at high pressures [21].…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…They also showed that the growth rate is governed by the shear stress, rather than the normal stress. This fact is confirmed by experiments showing that tribo-films do not grow in pure rolling contacts, not even at high pressures [21].…”
Section: Introductionmentioning
confidence: 58%
“…Inputs for the model are, in addition to the traditional mechanical properties of the substrate materials, the constants in the stress-activated Arrhenius equations and the constants a and C 1 in the wear equations. These constants depend on the type of additive, base oil, and concentration of ZDDP molecules [21,43]. It is important to notice that these constants may be independent of load or temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, primarily the zinc rich top layer will be worn during rubbing and as there are few (or none) iron ions available the new reaction layer will be formed with zinc as counter ion, leading to an equilibrium in the rates of formation and removal (Naveira‐Suarez et al . 2010). The initial WTW measured in sample ZDDP1, after 5 min rubbing, corresponds with the Hertzian contact diameter.…”
Section: Resultsmentioning
confidence: 99%
“…The same behavior was observed when using ZDDP in solution with commercial base oils of different polarities and among the operating conditions, shear was identified as a fundamental parameter on the activation of additives on rubbing steel surfaces and the properties of the derived reaction layer (Naveira‐Suarez et al . 2010). In this article, we study the evolution of the reaction layer with rubbing time and its nanofriction and nanowear behavior, to further understand the differences observed in the friction and wear performance.…”
Section: Introductionmentioning
confidence: 99%